Cardiac mass in a patient with sigmoid adenocarcinoma: a metastasis? - Ngow, Harris Abdullah; Wan Mohd Nowalid, Wan Khairina (Clinics - Cardive Publishing Co., 2012)
Cardiac metastasis from a bowel malignancy seldom occurs and there is a limited number of case reports published on this subject. Although colorectal cancer is the third commonest malignancy in Malaysia, the incidence of cardiac metastasis has never been reported. We report a case of an elderly man with recently diagnosed adenocarcinoma of the sigmoid colon, who presented with congestive cardiac failure secondary to mechanical obstruction by a right atrial mass. The intractable shock led to his sudden death before any intervention could be planned. If an intra-cavity cardiac mass is detected in a patient with an underlying metastatic malignancy, cardiac metastasis should be suspected. However, primary cardiac tumour or thrombus could also be the differential diagnosis. In our case, the definitive cardiac pathology remained unsolved as an autopsy was refused.